Properties of Bacillus cereus hemolysin II: a heptameric transmembrane pore. - Miles, G; Bayley, H; Cheley, S (2002)
The gene encoding hemolysin II (HlyII) was amplified from Bacillus cereus genomic DNA and a truncated mutant, HlyII(DeltaCT), was constructed lacking the 94 amino acid extension at the C terminus. The proteins were produced in an E. coli cell-free in vitro transcription and translation system, and were shown to assemble into SDS-stable oligomers on rabbit erythrocyte membranes and liposomes. The hemolytic activity of HlyII was measured with rabbit erythrocytes yielding an HC(50) value of 1.64 ng mL(-1), which is over 15 times more potent than staphylococcal alpha-hemolysin. HlyII(DeltaCT) was about eight times less potent than HlyII in this assay. Limited proteolysis of the oligomers formed by HlyII and HlyII(DeltaCT) on red cell membranes showed that the C-terminal extension is sensitive to digestion, while HlyII(DeltaCT) is protease resistant and migrates with an electrophoretic mobility similar to that of digested HlyII. HlyII forms moderately anion selective, rectifying pores (I(+80)/I(-80) = 0.57, 1 M KCl, pH 7.4) in planar lipid bilayers of diphytanoylphosphatidylcholine with a unitary conductance of 637 pS (1 M KCl, 5 mM HEPES, pH 7.4) and exhibits no gating over a wide range of applied potentials (-160 to +160 mV). In addition, it was demonstrated that HlyII forms a homoheptameric pore by using gel shift electrophoresis aided by a genetically encoded oligoaspartate tag. Although they share limited primary sequence identity (30%), these data confirm that HlyII is a structural and functional homolog of staphylococcal alpha-hemolysin.